The Effect of CPA-Based Multimedia Articulate Storyline Batik Motif on Elementary Students’ Mathematical Representation - Putri, Hafiziani Eka; Krisnawati, Nopi; Nuraeni, Fitri; Alindra, Afridha Laily; Hikmatunisa, Nenden Permas; Ravy, Hun (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Mathematical representation is a fundamental ability to develop students' thinking skills. But in reality, this ability is still low. The investigation aims to ascertain the impact of CPA-based articulated storyline multimedia on the Mathematical Representation Abilities (MRA) of elementary school students. The research uses CPA-based articulate storyline multimedia in learning activities. A type of experimental research with pre-experimental designs, one group pretest-posttest. 44 pupils from one of Karawang Regency's elementary schools in West Java made up the sample. Data were obtained through MRA tests in the form of descriptions, students' daily journals, interviews, and photo documentation of research activities. The MRA test questions used were valid and reliable. Based on Guilford's criteria, the results of the test validity and reliability calculation are in the high category (Retrieved from zero point eighty-four). Descriptive data analysis was conducted by finding the simple linear regression equation and the coefficient of determination. Inferential data analysis was performed with a t-test. Descriptive results showed that using CPA-based multimedia articulated storyline affected the Mathematical Representation ability (MRA) of elementary school students. Based on hypothesis testing, it is known that CPA-based articulate storyline multimedia significantly affects the mathematical representation skills of elementary school pupils. The implication from research is that multimedia articulate storylines based on CPA represent alternatives for enhancing elementary school pupils' mathematical representation ability in learning two-dimensional mathematics.